Studying the parameter gradient energy coefficient of Polyethylene glycol as a function of molecular weight with Freed Contribution - Malak Ali; Saygin Nuri; Shany Rajab (College of Education for Pure Sciences, 2020)
The gradient energy coefficient () has a main function in extracting the polymers properties to help us to innovate and manufacture new polymers and different process like coating, wetting, foaming, adhesion operations. The Cahn-Hilliard (CH) theory [1], represents the free energy profile of polymer surfaces or interfaces.  Considers the free energy profile of polymer surfaces or interfaces as inhomogeneous which has more than one phase. On the other hand, it has been used the Freed Bawendi contribution in conjunction with Cahn-Hilliard in treatment with architecture structure for polymers [2]. While Simha-Somcynsky (SS) theory describes the thermodynamic properties of both low and high molecular weights in terms of occupied site fraction (y) [3].  This study has been examined in the range of (313 -473) K temperatures and up to about (150) Mpa pressure. The quantitative success of our study is clearly appeared in the minimum and maximum deviations in the volume is 0.036 and 0.128 respectively.